Daya Juang Mahasiswa Asing - Wiwit Salindri Kusuma Wardani; Satih Saidiyah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2016)
This research aims to describe adversity quotient and its supporting factor among foreign students. Subjects are students from Thailand studying at State Islamic University Sunan Kalijaga Yogyakarta. This research applied qualitative approach using phenomenology in order to obtain the meaning of adversity quotient. The result shows some themes which are (1) controlling the problems by following many organizations, association, and remembering the struggles of parents, (2) being responsible for completing assignment, (3) being capable to limit the issue so that will not interfere other activities, and (4 ) being able to survive by having principle that there always be an easiness for every difficulties. Factors influencing the adversity quotient are self-motivation and support from surrounding especially parents, confidence to finish college well, and individual characters. Characters like quiet, shy and not confidence inhibiting adversity quotient while friendly and easy going supporting the adversity quotient.